2012
DOI: 10.1111/j.1365-2966.2011.20262.x
|View full text |Cite
|
Sign up to set email alerts
|

FR Cnc revisited: photometry, polarimetry and spectroscopy★

Abstract: This paper is part of a multiwavelength study aimed at using complementary photometric, polarimetric and spectroscopic data to achieve an understanding of the activity process in late‐type stars. Here, we present the study of FR Cnc, a young, active and spotted star. We performed analysis of All Sky Automated Survey 3 (ASAS‐3) data for the years 2002–08 and amended the value of the rotational period to be 0.826518 d. The amplitude of photometric variations decreased abruptly in the year 2005, while the mean br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…This type of behaviour is similar to that which has also been observed in some other active stars (e.g. Huovelin et al 1985;Huovelin & Saar 1988;Yudin & Evans 2002;Alekseev 2003;Rostopchina et al 2007;Golovin et al 2012;Patel et al 2013). The observed polarizations in these active dwarfs are also compa-rable to that of another class of active stars, namely RS CVn binaries (see Liu & Tan 1987, Scaltriti et al 1993).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This type of behaviour is similar to that which has also been observed in some other active stars (e.g. Huovelin et al 1985;Huovelin & Saar 1988;Yudin & Evans 2002;Alekseev 2003;Rostopchina et al 2007;Golovin et al 2012;Patel et al 2013). The observed polarizations in these active dwarfs are also compa-rable to that of another class of active stars, namely RS CVn binaries (see Liu & Tan 1987, Scaltriti et al 1993).…”
Section: Discussionsupporting
confidence: 89%
“…Evidence for a connection between linear polarization and magnetic activity indicators is lacking because on one hand the variation, as well as the mean degree of polarization of late-type dwarfs are very small, and on the other hand sizes of samples studied are small. Therefore, we have observed a sample of 50 active late type dwarfs and supplemented it with another sample of 18 active dwarfs, those are available in the literature (Huovelin et al 1985;Alekseev 2000Alekseev , 2003Golovin et al 2012;Patel et al 2013). The criteria of selection of stars in the sample were (i) the V -band magnitude range of 6.0 − 13.0 mag, and (ii) the (B − V ) colour range of 0.5 − 1.5 mag.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray light curve was folded with a period of 0.826518 days and at JD = 2452635.72669 as given Golovin et al (2012). The phase bin of the folded light curve was 0.05.…”
Section: X-ray Light Curvementioning
confidence: 99%
“…A few flaring events were also caught in the past in the optical band. Golovin et al (2012Golovin et al ( , 2007 detected a strong flare in B, V, R, and I filters, where peak flare flux in B band was found to be $ 37 times more than the quiescent flux. Later in 2010, Kozhevnikova et al (2018) reported one flare with flare duration of 32.5 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the X-ray light curve is variable with confidence limit of 99%. The X-ray light curve was folded with a period of 0.826518 days and at JD = 2452635.72669 as given Golovin et al (2012). The phase bin of the folded light curve was 0.05.…”
Section: X-ray Spectramentioning
confidence: 99%